Microcirculatory perfusion disturbances following cardiopulmonary bypass: a systematic review - den Os, Matthijs M.; van den Brom, Charissa E.; van Leeuwen, Anoek L. I.; Dekker, Nicole A. M. (Critical care (London, England), 2020)
Background Microcirculatory perfusion disturbances are associated with increased morbidity and mortality in patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). Technological advancements made it possible to monitor sublingual microcirculatory perfusion over time. The goal of this review is to provide an overview of the course of alterations in sublingual microcirculatory perfusion following CPB. The secondary goal is to identify which parameter of sublingual microcirculatory perfusion is most profoundly affected by CPB. Methods PubMed and Embase databases were systematically searched according to PRISMA guidelines and as registered in PROSPERO. Studies that reported sublingual microcirculatory perfusion measurements before and after onset of CPB in adult patients undergoing cardiac surgery were included. The primary outcome was sublingual microcirculatory perfusion, represented by functional capillary density (FCD), perfused vessel density (PVD), total vessel density (TVD), proportion of perfused vessels (PPV), and microvascular flow index (MFI). Results The search identified 277 studies, of which 19 fulfilled all eligibility criteria. Initiation of CPB had a profound effect on FCD, PVD, or PPV. Seventeen studies (89%) reported one or more of these parameters, and in 11 of those studies (65%), there was a significant decrease in these parameters during cardiac surgery; the other 6 studies (35%) reported no effect. In 29% of the studies, FCD, PVD, or PPV normalized by the end of cardiac surgery, and in 24% percent of the studies, this effect lasted at least 24 h. There was no clear effect of CPB on TVD and a mixed effect on MFI. Conclusion CPB during cardiac surgery impaired sublingual microcirculatory perfusion as reflected by reduced FCD, PVD, and PPV. Four studies reported this effect at least 24 h after surgery. Further research is warranted to conclude on the duration of CPB-induced microcirculatory perfusion disturbances and the relationship with clinical outcome. Trial registration PROSPERO, CRD42019127798